The efficacy and safety of combined administration of intravenous and topical tranexamic acid in primary total knee arthroplasty: a meta-analysis of randomized controlled trials - Huazhang Xiong (BMC Musculoskeletal Disorders, 2018)
Abstract Background The combined administration of intravenous (IV) and topical tranexamic acid (TXA) in primary total knee (TKA) knee remains controversial. The purpose of this meta-analysis was to assess the efficacy and safety of combined administration of IV and topical TXA in primary TKA. Methods PubMed, EMBASE, Cochrane Central Register of Controlled Trials, Web of Science, Google Search Engine and China National Knowledge Infrastructure databases were searched for randomized controlled trials (RCTs) were comparing the combined administration of IV and topical TXA following primary TKA. The primary outcomes were total blood loss, maximum hemoglobin drop, and deep venous thrombosis (DVT) and/or pulmonary embolism (PE). The second outcomes were drainage volume and transfusion requirements. Data were analyzed using RevMan 5.3. Results A total of 6 RCTs involving 701 patients were included in the meta-analysis. The combined group provided lower total blood loss (MD − 156.34 mL, 95% CI, − 241.51 to − 71.18; P = 0.0003), drainage volume (MD − 43.54 mL, 95% CI, − 67.59 to − 19.48; P = 0.0004), maximum hemoglobin drop (MD − 0.56 g/dl, 95% CI, − 0.93 to − 0.19; P = 0.003) than IV TXA alone. No significant difference were found in terms of transfusion requirements (RR 0.48, 95% CI, 0.16 to 1.44; P = 0.19), DVT (RR 1.01, 95% CI, 0.14 to 7.12; P = 0.99) and PE (RR 0.33, 95% CI, 0.01 to 7.91; P = 0.49) between the two group. Subgroup analyses shows that the combined group was less total blood loss in non-tourniquet (P = 0.0008), topical TXA dose > 1.5 g (P <  0.00001) and number of IV TXA ≥ 2 doses (P = 0.005) of TXA compared with the IV group alone. Conclusions The available evidence indicates combined group were associated with lower total blood loss, drainage volume, and maximum hemoglobin drop. A similar transfusion requirement was found in both groups. Subgroup analyses demonstrates that total blood loss was less in patients with non-tourniquet, topical TXA dose > 1.5 g and number of IV TXA ≥ 2 doses of TXA. There was no increase the rates of DVT and PE.